Quantifying vulnerability of sharks and rays species in Indonesia: Is biological knowledge sufficient enough for the assessment?. (May 2019) - Mardhiah, U; Booth, H; Simeon, B M; Muttaqin, E; Ichsan, M; Dharmadi,; Fahmi,; Prasetyo, A P; Yulianto, I
Abstract: Sharks and rays are vulnerable species, which are highly exploited in Indonesian waters but lacked of detailed information on their ecology and fisheries status. This research aims to assess the level of vulnerability of sharks and rays to overfishing using the maximum intrinsic rate of population increase (rmax ), derived from the Euler-Lotka equation, as a proxy of extinction risk. It is calculated based on several biological parameters including fecundity, maximum age, age at maturity, and the number of offspring. Using rmax calculation adapted to shark and ray life history traits by accounting for survival to maturity, we were able to calculate rmax values for 26 out of 208 sharks and rays species present in Indonesia. This includes vulnerable species such as Mobula alfredi, Prionace glauca, and Pristis zijsron. This result showed that rmax is a valuable tool which can be used to quantify extinction risk with some level of precision, but it also highlights the necessity to collect important biological information of the most vulnerable species to further estimate their status. This approach requires complementary information related to external threats such as habitat degradation, species economic value and threat level from local fishing effort and related fishing gears.